On the Formation of the Aesthetics of Old Russian Cursive Writing (Manuscript f. 115 no. 160 from St. Petersburg Institute of History) - Tsypkin, Denis O. (Actual Problems of Theory and History of Art, 2021)
The author addresses anew the manuscript f. 115 no. 160 from the collection of St. Petersburg Institute of History (the so-called ‘Azbuka Fryaskaya’) of 1604. This manuscript, written for the most part by the Muscovite scribe Fyodor Basov, is one of the two oldest Russian calligraphy sample books. The author discusses the relation of the ‘Azbuka Fryaskaya’ to other Old Russian ABC-books and their functions. As the codicological analysis has proved, the quires with cursive writing initially were placed in another part of the codex, next to the examples of ornate lettering. Such placement of the quires with cursive writing, as well as their decoration shows that Fyodor Basov viewed the cursive writing as decorative, ornate lettering par excellence. The paper also discusses the technical and aesthetical principles of the cursive writing, which were basic for Muscovite calligraphers of the late 16th — early 17th century when cursive writing took its shape as a style of writing. Special attention has been paid to the question of the influence of Greek (Byzantine) tradition on the aesthetics of Old Russian calligraphic cursive writing. Both the Russian calligraphic sample-books and the cursive writing are also viewed in the context of Western European calligraphy and its influence. The author concludes that the cursive writing style elaborated by the Muscovite calligraphers was the result of the development of Russian Early Modern writing culture that adopted some tendencies both from the Byzantine and from the Western traditions.